2017
DOI: 10.1002/lary.26818
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and rebound rates in propranolol‐treated subglottic hemangioma: A literature review

Abstract: Propranolol is efficacious for treating subglottic hemangiomas. Rebound growth does occur in a small subset of patients during the propranolol wean. Close observation for children during weaning of propranolol therapy for subglottic hemangioma is essential. Adjunctive management strategies need to be used in patients with rebound growth. Laryngoscope, 127:2665-2672, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
0
11
0
3
Order By: Relevance
“…A recent review of the literature by Schwartz et al in 2017 found a success rate of 88% among 49 patients treated in this way for SGH. The remaining 12% were treated with endoscopic debulking followed by open surgery (10). The same report documented a very low grade of rebound growth after drug administration (9%), and half of children experiencing such a problem recovered after having increased the pharmacological dosage (10).…”
Section: Endoscopic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of the literature by Schwartz et al in 2017 found a success rate of 88% among 49 patients treated in this way for SGH. The remaining 12% were treated with endoscopic debulking followed by open surgery (10). The same report documented a very low grade of rebound growth after drug administration (9%), and half of children experiencing such a problem recovered after having increased the pharmacological dosage (10).…”
Section: Endoscopic Treatmentmentioning
confidence: 99%
“…The remaining 12% were treated with endoscopic debulking followed by open surgery (10). The same report documented a very low grade of rebound growth after drug administration (9%), and half of children experiencing such a problem recovered after having increased the pharmacological dosage (10). Therefore, endoscopic and/or open-neck surgical treatment of SGH should be nowadays considered as the last option and performed only after failure of appropriate conservative medical treatment.…”
Section: Endoscopic Treatmentmentioning
confidence: 99%
“…Bei Erwachsenen wird typischerweise die hintere Glottis befallen, bei Kindern die vordere und die subglottische Region [35]. Makroskopisch handelt es sich um kleine (typischerweise < 2 cm große), gelblich-weiße, submuköse, abgegrenzte Gewebevermehrungen mit ödematös-hämorrhagischem Randsaum [34] [41,42]. Von anderen wird eine CO 2 -Lasertherapie als sehr erfolgversprechendes Therapiekonzept angesehen [43].…”
Section: Granularzelltumor (Gzt)unclassified
“…Das weibliche Geschlecht ist bevorzugt[42]. Ohne Therapie kommt es zur Atemwegsobstruktion und Mortalitätsraten um bis zu 50 %, wenn bei Kleinkindern die engste Stelle des Atemweges, d. h. die Subglottis betroffen ist[41,43]. Symptome sind Atemanstrengung, Stridor, Husten, Zyanose mit deutlichen Sauerstoffentsättigungen[42].…”
unclassified
“…The effectiveness of propranolol on cutaneous infantile haemangioma was first described by Léauté-Labrèze et al in 2008 4. Since then, the use of propranolol for the treatment of subglottic haemangioma has become hugely popular due to ‘its effectiveness and safety profile as compared with more traditional methods of treatment such as systematic and intralesional steroids, vincristine, bleomycin or interferon’ 5. ‘Laser and surgical excision are now reserved for unresponsive for acutely life-threatening haemangiomas’ 5.…”
Section: Introductionmentioning
confidence: 99%